Pengaruh Marketing Mix Terhadap Kepuasan Dan Loyalitas Konsumen Generasi Muda - R.Ferry Bakti Atmaja; Seno Hadi Saputro; R. Burham Isnanto; Ari Amir Alkodri (Magister Manajemen STIE Bank BPD Jateng, 2023)
The younger generation is increasingly playing an important role in many areas of life in line with the development of science and technology. In the economic field, youth has played a role as an economic driver, both as a businessman and as a potential target market for company owners. By understanding the right marketing strategy according to the character of this segment, the company will be able to gain increased market share and long-term profits. This research is a quantitative study intending to find the effect of the marketing mix strategy consisting of Product, Price, Place, Promotion, People, Process and Physical Evidence on customer satisfaction and loyalty in the culinary field. Data was collected using a questionnaire technique and analyzed through Moderated Regression Analysis. The results of this study are that Promotion has an effect of 0.374 on loyalty, People has an effect of 0.172 and Place has an effect of 0.240 while other factors cannot be proven to have an effect. The Satisfaction variable is only able to mediate and strengthen the influence on the People factor